Pelatihan Fundamental Coaching Bagi Pelatih bola basket di kabupaten Lombok Timur - hulfian, lalu; Syobri, Nazalus; Nurdin; Pudak Wangi, Sekar; Lukman (Jurnal Pengabdian Keolahragaan dan Sains, 2025)
Fundamental coaching training for extracurricular basketball coaches in East Lombok Regency was conducted to improve their basic coaching competencies and knowledge. The main problem faced is the lack of licensed coaches, resulting in training practices that rely heavily on personal experience, which are less optimal and outdated. The training was held at GOR Ananda Masbagik, involving teachers and basketball coaches from junior high to senior high schools. The method included structured theory and practical sessions, along with evaluations using pretest and posttest instruments. The results showed a significant improvement in participants' knowledge of basic coaching principles and basketball training management. The training also facilitated discussions and networking among coaches to support sustainable development. This activity is expected to be an initial step in developing basketball coaching capacity in East Lombok, thereby optimizing and sustaining athlete development processes.